Prolactin regulates H3K9ac and H3K9me2 epigenetic marks and miRNAs expression in bovine mammary epithelial cells challenged with Staphylococcus aureus - Barajas-Mendiola, Marco Antonio; Salgado-Lora, María Guadalupe; López-Meza, Joel Edmundo; Ochoa-Zarzosa, Alejandra (Frontiers in Microbiology, 2022)
Epigenetic mechanisms are essential in the regulation of immune response during infections. Changes in the levels of reproductive hormones, such as prolactin, compromise the mammary gland’s innate immune response (IIR); however, its effect on epigenetic marks is poorly known. This work explored the epigenetic regulation induced by bovine prolactin (bPRL) on bovine mammary epithelial cells (bMECs) challenged with Staphylococcus aureus. In this work, bMECs were treated as follows: (1) control cells without any treatment, (2) bMECs treated with bPRL (5 ng/ml) at different times (12 or 24 h), (3) bMECs challenged with S. aureus for 2 h, and (4) bMECs treated with bPRL at different times (12 or 24 h), and then challenged with S. aureus 2 h. By western blot analyses of histones, we determined that the H3K9ac mark decreased (20%) in bMECs treated with bPRL (12 h) and challenged with S. aureus, while the H3K9me2 mark was increased (50%) in the same conditions. Also, this result coincided with an increase (2.3-fold) in HDAC activity analyzed using the cellular histone deacetylase fluorescent kit FLUOR DE LYS®. ChIP-qPCRs were performed to determine if the epigenetic marks detected in the histones correlate with enriched marks in the promoter regions of inflammatory genes associated with the S. aureus challenge. The H3K9ac mark was enriched in the promoter region of IL-1β, IL-10, and BNBD10 genes (1.5, 2.5, 7.5-fold, respectively) in bMECs treated with bPRL, but in bMECs challenged with S. aureus it was reduced. Besides, the H3K9me2 mark was enriched in the promoter region of IL-1β and IL-10 genes (3.5 and 2.5-fold, respectively) in bMECs challenged with S. aureus but was inhibited by bPRL. Additionally, the expression of several miRNAs was analyzed by qPCR. Let-7a-5p, miR-21a, miR-30b, miR-155, and miR-7863 miRNAs were up-regulated (2, 1.5, 10, 1.5, 3.9-fold, respectively) in bMECs challenged with S. aureus; however, bPRL induced a down-regulation in the expression of these miRNAs. In conclusion, bPRL induces epigenetic regulation on specific IIR elements, allowing S. aureus to persist and evade the host immune response.